Concreting deep lifts and large volume pours - Bamforth, P. B (CIRIA report)
This report presents recommendations for the construction of deep lifts and large volume pours. The intention is to ensure that designers, contractors and concrete producers are aware of the features of these construction methods, whilst providing guidance on how to avoid potential problems.